Value of the cytological study in thyroid nodules - Delgado, Bolivar; Yametti, Luis; Berasategui, Ruber (Cirugía del Uruguay, 1982)
A series of 187 cases was studied. The value of cytology; by puncture of a thyroid nodule without side extrathyroid manifestations; to diagnose cancer is analyzed. Compared to foreign issues that show a high percentage of positive results, in our enviroment tlús procedure under these circumstances is of little diagnostic value.